2013
DOI: 10.1073/pnas.1303760110
|View full text |Cite
|
Sign up to set email alerts
|

Monoallelic loss of tumor suppressor GRIM-19 promotes tumorigenesis in mice

Abstract: Significance Gene-associated with retinoid-interferon induced mortality-19 (GRIM-19) is an interferon-retinoid–regulated growth suppressor that inhibits cell growth by targeting the transcription factor STAT3 for inhibition. In primary human tumors GRIM-19 is suppressed or mutated, leading to constitutive STAT3 activity and indicating the tumor-suppressive function of GRIM-19. To understand the in vivo role of Grim-19 in tumor development, we generated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 97 publications
1
41
0
Order By: Relevance
“…To date, three biological STAT3 inhibitors including suppressor of cytokine signaling 3 (SOCS3) [39, 40, 42], protein inhibitor of activated STAT3 (PIAS3) [41, 42], and GRIM-19 [2629, 42] have been reported. However, tumor-suppressive roles of SOCS3 and PIAS3 have not yet been established [42]. It is therefore of interest in our current study to focus on the role of GRIM-19 in gastric carcinogenesis and its correlation with STAT3 activation in GC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, three biological STAT3 inhibitors including suppressor of cytokine signaling 3 (SOCS3) [39, 40, 42], protein inhibitor of activated STAT3 (PIAS3) [41, 42], and GRIM-19 [2629, 42] have been reported. However, tumor-suppressive roles of SOCS3 and PIAS3 have not yet been established [42]. It is therefore of interest in our current study to focus on the role of GRIM-19 in gastric carcinogenesis and its correlation with STAT3 activation in GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, pharmacological inhibition of STAT3 did not completely abrogate GRIM-19 loss-driven tumorigenesis, suggesting that the full capacity of GRIM-19 loss to tumor growth may extend beyond its ability to activate STAT3. Since GRIM-19 loss also contributed to the switch between oxidative and glycolytic pathways [36, 42, 43], while aberrant glycolytic metabolism provides tumor growth advantages [4446]. Therefore, compensatory activation of these contributions by GRIM-19 loss may provide a reasonable account for the GRIM-19 loss-driven tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Even, a mono-allelic loss was sufficient for tumor development. A significant decline of mitochondrial electron transport machinery viz., RC-2, RC-4 (cytochrome’c oxidase) and RC-5 (ATP synthase) and a modest increase in RC-3 (cytochrome’c reductase) levels occurred in the absence of GRIM-19 [118]. These are consistent with a strong decline in oxygen consumption in these cells.…”
Section: The Mitochondrial Function Of Grim-19mentioning
confidence: 61%
“…We have shown that conditional deletion of Grim-19 in adult mouse skin does not cause significant lethality. However, these mice are highly prone to chemically-induced tumor development [118]. Even, a mono-allelic loss was sufficient for tumor development.…”
Section: The Mitochondrial Function Of Grim-19mentioning
confidence: 99%
See 1 more Smart Citation